Объяснение:
A1.
a) (5a+10)/(b-7):(a²+4a+4)/2b-14=(5(a+2)/(b-7) * ((2(b-7))/(a²+4a+4)=
=(5(a+2)2(b-7))/((b-7)(a+2)²)=5*2/(a+2)=10/(a+2)
a²+4a+4=0; D=16-4*1*4=0
a₁=a₂=0,5(-4±√0)= -2
a²+4a+4=(a+2)(a+2)=(a+2)²;
б) (√50-√6)/√12=(√(25*2)-√(3*2))/(√3*2*2)=(5√2-√(3*2))/(√3*2*2)=
=(5-√3)/√6=(√6(5-√3)/6=(5√(3*2)-√(3*3*2))/6=(5√6-3√2)/6.
A2.
а) (√2)⁶/32=(2¹⁽²)⁶/2⁵=2³/2⁵=2³⁻⁵=2⁻²=1/2²=1/4;
б) (5,2*10⁻⁷)(3,5*10⁴)=5,2*3,5*10⁻⁷⁺⁴=18,2*10⁻³=1/(18,2*10³);
в) 3⁻⁶*9⁻²/(3⁻¹²)=3⁻⁶*(3²)⁻²/3⁻¹²=3⁻⁶*3⁻⁴/3⁻¹²=3⁻¹⁰/3⁻¹²=3⁻¹⁰⁻⁽⁻¹²⁾=3⁻¹⁰⁺¹²=3²=
=9.
А3.
x²+2x=16x-49;
x²+2x-16x+49=0;
x²-14x+49=0;
x²-2*7x+7²=0;
(x-7)²=0;
x₁=x₂=7.
B1.
x³-3x²-4x+12=0;
(x³-3x²)-(4x-12)=0;
x²(x-3)-4(x-3)=0;
(x-3)(x²-4)=0;
x-3=0; x=3;
x²-4=0; x²=4; x=±√4; x=±2;
x₁=-2; x₂=2; x₃=3
a1=180/(1+q)(1+q²)
a3-a1=36⇒a1q²-a1=36⇒a1(q²-1)=36⇒a1=36/(q+1)(q-1)
180/(1+q)(1+q²)=36/(1+q)(q-1)⇒
5/(1+q²)=1/(q-1)
1+q²=5q-5
q²-5q+6=0
q1+q2=5 U q1*q2=6
1)q1=2⇒a1=36/3=12
12;24;48;96
2)q2=3⇒a1=36/8=4,5
4,5;13.5;40,5;121,5